Senam Hipertensi Untuk Mencegah Penyakit Hipertensi Pada Masyarakat - Pae, Kristina; Joewono, Andrew; Astarini, Made Indra Ayu; Mare, Agustina Chriswinda Bura (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2024)
Hypertension exercise is one of the non-pharmacological therapies that helps vasodilation and increase elasticity in blood vessels so that blood pressure decreases. This activity was carried out with the aim of increasing knowledge and the role of active participants in preventing hypertension through hypertension exercise. The activity was carried out on November 30, 2024. The participants were 32 elderly and elderly companion cadres. The methods used were lectures, conferences, and discussions. Evaluation activities were carried out by observing participants in doing gymnastics, measuring blood pressure before and after doing gymnastics, and providing pretest and posttest questionnaires. The participants were very enthusiastic in doing gymnastics movements and were able to follow the directions of the gymnastics instructor. The results of the implementation team's observations showed that as many as 10 participants (76.9%) of the 13 people who took part in hypertension gymnastics were able to follow the gymnastics movements correctly. A total of 8 participants (61.5%) experienced a decrease in blood pressure after doing hypertension exercises, and the participants' scores increased by 5 to 8 points. From this activity, it can be concluded that hypertension exercises help lower participants' blood pressure.